Analysis of Human Resource Development in Improving Employee Performance at the Wiraland Property Group - Yeni Rachmawati; Della Monika Sembiring; Eka Wulandari Surbakti (Jurnal Ekonomi, 2022)
This study aims to determine what factors influence human resource development in improving employee performance at Wiraland Property Group. The indicators used in this study are indicators of human resource development, namely motivation, personality, and skills. As for the employee performance variables, the indicators used are quality, quantity, time, cost suppression, supervision, and relations between employees. The type of data used by researchers is primary data sourced from internal and external data. Methods of data collection using field research methods, through questionnaires and literature research. Methods of data analysis using quantitative methods. The results of the study show that the development of human resources has a significant effect or plays a very important role in improving employee performance. The suggestion in this research is to make a program.